Expediency of immunocytochemical study as a marker of proliferative activity in cervical intraepithelial neoplasia - Tatyana Yu. Pestrikova; Ainur F. Ismaylova (IP Berlin A.V., 2022)
Aim. To assess the feasibility of using immunocytochemical studies as a marker of proliferative activity in cervical intraepithelial neoplasia. Materials and methods. A comprehensive examination of 78 women, aged 25 to 45 years, with the presence of cervical intraepithelial neoplasia was carried out. Verification of the diagnosis was carried out on the basis of data from clinical, cytological, colposcopic, histological studies. Human papillomavirus typing was carried out using the polymerase chain reaction method (Kvant 21 test). Results. The results obtained in our study indicate that in patients with CIN II, III, chronic cervicitis associated with human papillomavirus (HPV) is an obligatory background pathology. Regardless of the severity of cervical dysplasia (CIN IIIII), among the various types of HPV, HPV type 16 and associations of various HPV types of high oncological risk prevailed (41.03 and 25.64%, respectively). The HPV load result was expressed in decimal logarithms (Lg). Co-expression of p16ink4a oncoprotein and proliferative activity marker Ki-67 in epithelial cells was observed at viral load parameters of 35 Lg in 64.10% of cases, and at values of 5 Lg in 100% of cases. Conclusion. Our data indicate the need for wider use of non-invasive determination of markers р16ink4a and Ki-67 during primary screening, which will improve the tactics of managing patients with cervical precancer. Persistent course of human papillomavirus in patients with cervical intraepithelial neoplasia II in the presence of signs of coexpression of p16ink4a and Ki-67 dictates the inexpediency of performing cervical excision with subsequent control after 6 months.